Ethical considerations in modern rehabilitation medicine - Ohry, Avi (Rehabilitacija (Ljubljana), 2017)
The paper provides a short overview of ethical principles and models in modern medicine in general, and specific ethical and practical models in rehabilitation medicine. It highlights the various ethical issues in modern rehabilitation medicine and provides some general considerations on bioethics at present and in the future.
Keywords: bioethics; bioetika; ethical models; ethical principles; ethical problems; ethics; etična načela; etični modeli; etični problemi; Physical and Rehabilitation Medicine; rehabilitacijska medicina; rehabilitation medicine